The biobehavioral family model with a seminarian population: A systems perspective of clinical care - Smith, Kaitlin; Wang, David; Canada, Andrea; Poston, John M.; Bee, Rick; Hurlbert, Lara (Frontiers in Psychology, 2022)
Seminary students remain unstudied in the research literature despite their eminent role in caring for the wellbeing of congregants. This study aimed to conduct baseline analysis of their family of origin health, psychological health, and physiological heath by utilizing the Biobehavioral Family Model (BBFM; Wood, 1993) as a conceptual framework for understanding the associations between these constructs. Statistical analysis utilizing structural equation modeling provided support that the BBFM was a sound model for assessing the relationships between these constructs within a seminary sample. Additionally, seminarians were found to have higher rates of anxiety and depression when compared to the general population. Together, findings indicate that clinical care for seminarians may be best if implemented from a global systemic perspective.